Analisis Motivasi Karyawan Terhadap Kinerja Pada Perusahaan CV. Satria Jaya Food - Rijalludin Rijalludin; Wardana Wardana (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
This study aims to analyze employee motivation towards improving performance at Cv. Satria Jaya Food (Sjf) company. The method used is a descriptive qualitative research method with a sample of 18 people. The data collection technique used was interviews. The data analysis method used is data collection, data reduction, display data, and conclusion assessment to explain the relationship between Employee Motivation to Performance Improvement. The results showed that the influence of Employee Motivation on Performance Improvement had positive results based on the results of data processing which showed that there was an influence between Employee Motivation on Performance Improvement.